Предмет: Алгебра,
автор: lovethecat1618
решитеее пожалуйстаааа!!!!!!!
Приложения:
Ответы
Автор ответа:
1
y(кас) = f'(x0) × (x - x0) + f(x0)
f'(x) = y' = 2 - 2x
1. f'(x0) = f'(2) = 2 - 4 = -2
f(x0) = 3
y(кас) = -2x + 4 + 3
y(кас) = -2x + 7
2. f'(x0) = f'(1) = 0
f(x0) = -2
y(кас) = 0x - 0 - 2 = -2
lovethecat1618:
можете помочь еще с 5 заданиями? так как идет ограничение на кол-во примеров.
Похожие вопросы
Предмет: Обществознание,
автор: lbrbtcrhbxths2006
Предмет: Українська мова,
автор: tana13097
Предмет: Физика,
автор: vitalinaiakubiv
Предмет: Биология,
автор: Андрій111234